1995
DOI: 10.1093/infdis/171.6.1497
|View full text |Cite
|
Sign up to set email alerts
|

A Multistate Outbreak of Oyster-Associated Gastroenteritis: Implications for Interstate Tracing of Contaminated Shellfish

Abstract: In November 1993, clusters of gastroenteritis in six states following oyster consumption were investigated to identify common features, and stool samples were obtained to identify a pathogen. Efforts were made to account for all potentially contaminated oysters using harvest tags and the interstate recall system. Consumption of oysters was associated with illness in 10 clusters; no other food was implicated. A Norwalk-like virus was detected by electron microscopy in 9 of 18 samples and by reverse transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(63 citation statements)
references
References 22 publications
2
61
0
Order By: Relevance
“…NLV infections often result from ingesting contaminated food (14,30), such as oysters (4,8) and water (3,33), or by person-to-person transmission in semiclosed communities, such as hospitals (35), schools (20), nursing homes (18), and cruise ships (12).…”
mentioning
confidence: 99%
“…NLV infections often result from ingesting contaminated food (14,30), such as oysters (4,8) and water (3,33), or by person-to-person transmission in semiclosed communities, such as hospitals (35), schools (20), nursing homes (18), and cruise ships (12).…”
mentioning
confidence: 99%
“…Epidemiological investigations of outbreaks have shown that the most important modes of transmission are person-to-person contacts and contaminated food and water (20,31). Multistate and global outbreaks linked to the distribution of contaminated foods and water have been reported (4,6,14,45). Moreover, the emergence of a common strain with global distribution has raised important questions on the likelihood of massive food-borne introduction of new NLV strains (43,51).…”
mentioning
confidence: 99%
“…Refrigeration paradoxically increases the pathogens' geographic range, permitting transport of apparently healthy seafood to many geographic areas, thus extending and prolonging outbreaks. Inadequate procedures for tracing and recall of contaminated seafood also serve to extend outbreaks (Dowell et al, 1995;Sugieda et al, 1996).…”
Section: Microbial Seafood Contaminationmentioning
confidence: 99%